I found a proof that if a heuristic $h$ is consistent, then it is admissible, but I'm confused by one of the steps in the proof.
The proof is by induction on $k$, the number of actions from a node $n$ to the goal node $G$.
Base step: $k = 1$, i.e., node $n$ is one step from $G$. Since the heuristic function $h$ is consistent,
$$h(n) \leq c(n, a, G) + h(G)$$
Since $h(G) = 0$,
$$h(n) \leq c(n, a, G) = h^{\ast}(n)$$
Therefore, $h$ is admissible.
Induction step: Assume: If $h(n′)$ is consistent, then $h(n′)$ is admissible, for all nodes $n′$ that are $k$ steps from $G$.
$$h(n) \leq c(n, a, n') + h(n')$$
Since $n′$ is $k$ steps from $G$ and $h$ is admissible for node $n′$ that is $k$ steps from $G$,
$$h(n') \leq h^{\ast}(n')$$ $$\implies c(n,a,n') + h(n') \leq c(n, a, n') + h^{\ast}(n')$$ $$\implies h(n) \leq c(n, a, n') + h^{\ast}(n') = h^{\ast}(n)$$
hence, $h$ us admissible for node n.
I'm specifically confused about these lines:
$$h(n) \leq c(n, a, G) = h^{\ast}(n)$$
and
$$h(n) \leq c(n, a, n') + h^{\ast}(n') = h^{\ast}(n)$$
How do we know that $c(n,a,G) = h^{\ast}(n)$? Wouldn't it depend on the action $a$ chosen?
Also, how do we know: $c(n, a, n') + h^{\ast}(n') = h^{\ast}(n)$?